3-Iodoaniline - Ferhan Slamang; Eric Cyriel Hosten; Richard Betz (IUCrData)
The title compound, C6H6IN, is the meta-iodinated derivative of aniline. The asymmetric unit contains two molecules. The structure was refined as a two-component inversion twin with a volume ratio of 55.6:44.4. In the crystal, cooperative hydrogen bonds of the N–H...N type connect the molecules into infinite chains propagating along the a-axis direction. Dispersive I...I contacts extend these chains to sheets perpendicular to the crystallographic c axis.